Arabidopsis ACTIN-DEPOLYMERIZING FACTOR3 Is Required for Controlling Aphid Feeding from the Phloem . Issue 1 (10th November 2017) - Mondal, Hossain A.; Louis, Joe; Archer, Lani; Patel, Monika; Nalam, Vamsi J.; Sarowar, Sujon; Sivapalan, Vishala; Root, Douglas D.; Shah, Jyoti
Abstract : Green peach aphid feeding from the sieve elements is shown to be restricted by ACTIN-DEPOLYMERIZING FACTOR3, thus implicating actin-dependent process in controlling insect feeding from the phloem. Abstract: The actin cytoskeleton network has an important role in plant cell growth, division, and stress response. Actin-depolymerizing factors (ADFs) are a group of actin-binding proteins that contribute to reorganization of the actin network. Here, we show that the Arabidopsis ( Arabidopsis thaliana ) ADF3 is required in the phloem for controlling infestation by Myzus persicae Sülzer, commonly known as the green peach aphid (GPA), which is an important phloem sap-consuming pest of more than fifty plant families. In agreement with a role for the actin-depolymerizing function of ADF3 in defense against the GPA, we show that resistance in adf3 was restored by overexpression of the related ADF4 and the actin cytoskeleton destabilizers, cytochalasin D and latrunculin B. Electrical monitoring of the GPA feeding behavior indicates that the GPA stylets found sieve elements faster when feeding on the adf3 mutant compared to the wild-type plant. In addition, once they found the sieve elements, the GPA fed for a more prolonged period from sieve elements of adf3 compared to the wild-type plant. The longer feeding period correlated with an increase in fecundity and population size of the GPA and a parallel reduction in callose deposition in the adf3 mutant. The adf3 -conferred susceptibility to GPA was overcome by expression of the ADF3 coding sequence from the phloem-specific SUC2 promoter, thus confirming the importance of ADF3 function in the phloem. We further demonstrate that the ADF3 -dependent defense mechanism is linked to the transcriptional up-regulation of PHYTOALEXIN-DEFICIENT4, which is an important regulator of defenses against the GPA.